2022
DOI: 10.52880/sagakaderg.1153674
|View full text |Cite
|
Sign up to set email alerts
|

Çocuk acil servisine yeniden başvuran vakaların demografik ve klinik özelliklerinin değerlendirilmesi

Abstract: Giriş: Acil Servislere Yeniden Başvuru Oranı (ASYBO) belli bir zaman periyodunda tekrar gelen/getirilen hastaların toplam hastaya oranı olarak tanımlanmıştır. Genellikle ilk 24 ya da 72 saat, bazı çalışmalarda da 7 gün ölçüme esas alınmaktadır. Materyal ve Metot: 2021 yılı 12 aylık çocuk acil servis başvuruları çalışmaya alındı. Veriler hasta protokol sayı temel alınarak, SQL yöntemiyle hastane bilgi sistemi veri tabanından elde edildi. Aynı hasta no’ya ait protokollerin 2021 yılı içinde geliş zamanları … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Studies have demonstrated an increase in forensic cases related to trauma among adults during the summer months, attributed to increased physical activity. 3 Similarly, in this study, a higher number of forensic cases was observed during the summer season, which corresponds to a holiday period. This can be attributed to individuals spending more time outside their homes due to the warm weather.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Studies have demonstrated an increase in forensic cases related to trauma among adults during the summer months, attributed to increased physical activity. 3 Similarly, in this study, a higher number of forensic cases was observed during the summer season, which corresponds to a holiday period. This can be attributed to individuals spending more time outside their homes due to the warm weather.…”
Section: Resultssupporting
confidence: 60%
“…Among these cases, the researchers found that exposure to assault/violence, burns, and drug poisoning were frequently encountered. 1,3,12 According to data from the Turkish Statistical Institute in 2021, forensic cases such as external injuries and poisoning resulted in a significant number of deaths among children. 13 In previous studies, 2,14,15 the prevalence of pediatric forensic cases among all forensic cases varied between 18% and 54.6%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations